L-Canavanine, a Root Exudate From Hairy Vetch (Vicia villosa) Drastically Affecting the Soil Microbial Community and Metabolite Pathways - Mardani-Korrani, Hossein; Nakayasu, Masaru; Yamazaki, Shinichi; Aoki, Yuichi; Kaida, Rumi; Motobayashi, Takashi; Kobayashi, Masaru; Ohkama-Ohtsu, Naoko; Oikawa, Yosei; Sugiyama, Akifumi; Fujii, Yoshiharu (Frontiers in Microbiology, 2021)
L-canavanine, a conditionally essential nonproteinogenic amino acid analog to L-arginine, plays important roles in cell division, wound healing, immune function, the release of hormones, and a precursor for the synthesis of nitric oxide (NO). In this report, we found that the L-canavanine is released into the soil from the roots of hairy vetch (Vicia villosa) and declines several weeks after growth, while it was absent in bulk proxy. Hairy vetch root was able to exudate L-canavanine in both pots and in vitro conditions in an agar-based medium. The content of the L-canavanine in pots and agar conditions was higher than the field condition. It was also observed that the addition of L-canavanine significantly altered the microbial community composition and diversity in soil. Firmicutes and Actinobacteria became more abundant in the soil after the application of L-canavanine. In contrast, Proteobacteria and Acidobacteria populations were decreased by higher L-canavanine concentration (500 nmol/g soil). Prediction of the soil metabolic pathways using PICRUSt2 estimated that the L-arginine degradation pathway was enriched 1.3-fold when L-canavanine was added to the soil. Results indicated that carbon metabolism-related pathways were altered and the degradation of nitrogen-rich compounds (i.e., amino acids) enriched. The findings of this research showed that secretion of the allelochemical L-canavanine from the root of hairy vetch may alter the soil microbial community and soil metabolites pathways to increase the survival chance of hairy vetch seedlings. This is the first report that L-canavanine acts as an allelochemical that affects the biodiversity of soil microbial community.